Microwave-Energy-Based Device for the Treatment of Cellulite and Localized Adiposity: Recommendations of the “Onda Coolwaves” International Advisory Board - Klaus Hoffmann; Elena Zappia; Paolo Bonan; Federica Coli; Luigi Bennardo; Matteo Tretti Clementoni; Valerio Pedrelli; Domenico Piccolo; Irina Poleva; Benedetta Salsi; Cristina Cuciti; Maria Stella Tarico; et al. (Bioengineering)
The body contour market has grown rapidly in recent years, due to persistent requests for noninvasive treatments for localized fat adiposities, cellulite, and skin laxity. A variety of different methods are now available to improve body shaping. This review aims to provide an exhaustive compendium of the main recommendations for the optimal use of an innovative device delivering microwaves (MWs) for unwanted fat and cellulite reduction (Onda Coolwaves, DEKA, Florence, Italy), resulting from the experiences of the most expert international users. The availability of this new technology has led to an increasing number of treated patients and clinical studies. However, what is still missing, to the best of our knowledge, is an evaluation of the long-term efficacy and safety of this method. Based on the most recent data available, this compendium focuses on the ideal parameters, patient selection, and treatment methodology for providing safe and effective treatment protocols. Future research findings may suggest changes to the conclusions or recommendations in this report.